Environmental Social Responsability with the Arborization of the University Campus, Piura-Perú - ELERA OJEDA, ROSARIO NELLY; Guerra Delgado, Marco Sergio; Carrasco Peña, Víctor Cruz; Domínguez Córdova, Joel; Guerra Delgado, Fernanda Belen (Emerging Trends in Education, 2022)
The University Social Responsibility is a management policy that aims to integrate transversely the different areas of the university, within the three impacts (social, economic and ecological) arises from the need to include the three strata of the university: teachers, administrators and students to raise awareness in caring for the environment and the importance of trees in our ecosystem. The objective is to improve the environmental conditions of the campus of the Universidad Nacional de Piura and to raise awareness among the university population about the preservation of the environment. Quantitative, exploratory and transversal study, measuring the fulfillment of the programmed activities (fertilization, irrigation, weeding, growth control, etc.). Of the 200 plants, only 180 (90%) were developed and of the 85 participants (students, teachers and administrative personnel), 80% (68 participants) complied with the indicators and objectives set. The collective environmental awareness of the teachers, students and administrative staff was shown by their active participation in the different activities carried out, such as planting, protection and care of trees to improve the ornamentation and environment of the university campus. The participants noted the improvement in the quality of life and the positive significance of planting trees, providing shade and fresh air that improved the climate of this hot northern Peruvian city. Keywords: Arborization; reforestation; awareness; environmental responsability; environment